Tari Topeng Karakter Sebagai Media Komunikasi Visual Bagi Guru Paud - Reni Rahmawati (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
This research aims to investigate the forms of dance performance and the impact of using mask dance as a visual communication medium for early childhood education (PAUD) teachers. With a focus on dance skills as a form of nonverbal communication involving movement, rhythm, expression, level, and floor patterns, the study aims to understand how dance can effectively convey messages to the audience, particularly in the context of early childhood education. The research employs a qualitative approach with a descriptive research design. Qualitative methodology is chosen to deepen the understanding of this phenomenon and describe its characteristics in detail. The descriptive research type is utilized to provide a comprehensive overview of the forms of performance and the impact of mask dance. The anticipated results of this research are expected to provide a deeper insight into the contribution of dance in the context of early childhood education. The information obtained from the analysis of performance forms and the influence of mask dance can serve as a foundation for PAUD teachers to develop more creative and effective teaching strategies, enhance children's engagement in the learning process, and enrich their educational experiences.